Miscellaneous azo dyes: a comprehensive review on recent advancements in biological and industrial applications. (March 2022) - Alsantali, Reem I.; Raja, Qandeel Alam; Alzahrani, Abdullah Y.A.; Sadiq, Amina; Naeem, Nafeesa; Mughal, Ehsan Ullah; Al-Rooqi, Munirah M.; El Guesmi, Nizar; Moussa, Ziad; Ahmed, Saleh A.
Abstract: Azo dyes, compounds having double bond linkage between two nitrogen atoms, are widely found as a main scaffold in a massive library of organic species that exhibit promising industrial and biological properties. Due to the numerous potential applications accredited to the azo function, there has been a significant surge in designing novel azo dyes and introducing advanced synthetic routes for their preparation, as well as investigating their diverse properties and seeking potential new applications for this class of compounds. This systematic review contains two parts and is set apart from the classic azo reviews in several aspects. The first part focuses on the biological affinities of azo dyes, while the second part covers the industrial applications of these molecules. In this review, we consolidate and highlight the significant applications of novel azo dyes in biological as well as in industrial fields. It is expected that this review will be helpful in future research to develop more potent multifunctional azo dyes. Graphical abstract: Image 1 Highlights: Azo dyes represent the largest production volume of dye chemistry. They are considered as fascinating motifs in organic chemistry. They gained massive attraction due to their versatile bio- and industrial applications. Substitution effect on the SAR was established according to IC50 values. The future perspectives of azo dyes were also pointed out.